Pengaruh Variasi Konsentrasi Tepung Bonggol Pisang Termodifikasi dengan Metode Enzimatis sebagai Bahan Substitusi pada Pembuatan Mi Basah - Widyaningsih, Arum Dewi; Abdillah, Hamid (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
The banana tuber contains high carbohydrates, but it is still rarely used because of the brown color of the flour due to heating. To cover this deficiency, modification with α-amylase enzyme was carried out. The purpose of this study was to obtain a suitable formulation for the manufacture of wet noodles that meet the requirements of SNI quality standards. The treatment variation made was the ratio of 3 tapioca: 9 banana tuber: 48 wheat (80% wheat), 3 tapioca: 6 banana tuber: 21 wheat (70% wheat), 3 tapioca: 5 banana tuber: 12 wheat (60% wheat). The variation of α-amylase enzyme used was 10%, 20%, 30%, 40% with 0% as the control variable. Organoleptic test to determine the most preferred noodle variation. The test parameters were color, aroma and texture. The results showed that the best quality with color and aroma wet noodles were obtained from a combination of 60% with 40% α-amylase enzyme concentration ratio. As the texture parameters were obtained from a combination of 60% wheat with 10% α-amylase enzyme concentration ratio. The results showed that the moisture content of wet noodles had met the SNI 2987:2015 standard, which is below 65%.